2014
DOI: 10.20467/1091-5710.18.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Caring-based Nursing Model in an Interdepartmental Setting to Improve Patient Satisfaction

Abstract: Caring is viewed as the essence of nursing. However caring is not a phenomenon exclusive to nurses. Hospitalized patients encounter numerous people in addition to nurses and each role and individual make an impact upon the care of the patient. These encounters can dramatically influence the level of satisfaction a patient feels about their hospital experience. The purpose of this study was to determine if implementing an interdepartmental caring-based approach based on Jean Watson’s theory of human caring coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patient satisfaction is related to the quality of hospital services. Patient satisfaction with nursing care is considered a principal outcome indicator of quality of care (Laschinger, Hall, Pedersen, & Almost, 2005), and it is seen as an important aspect for evaluating and improving overall healthcare (Dudkiewicz, 2014;Koy, Yunibhand, & Angsuroch, 2016). As nurses provide the key aspects of healthcare, their contribution influences significantly the level of patient satisfaction with the overall healthcare services provided.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Patient satisfaction is related to the quality of hospital services. Patient satisfaction with nursing care is considered a principal outcome indicator of quality of care (Laschinger, Hall, Pedersen, & Almost, 2005), and it is seen as an important aspect for evaluating and improving overall healthcare (Dudkiewicz, 2014;Koy, Yunibhand, & Angsuroch, 2016). As nurses provide the key aspects of healthcare, their contribution influences significantly the level of patient satisfaction with the overall healthcare services provided.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Canam () has suggested that nurses are working in ‘practice environment[s] dominated by a biomedical model of healthcare and a technical discourse in which objective/technical knowledge is privileged [leading to] subjective/experiential knowledge [being] discounted’ (p. 298). It is within such socially constructed healthcare environments that nurses attempt to make meaning of how to incorporate person‐centered care and being caring professionals, which requires they develop trusting relationships with people (Allen, ; Dahlke & Stahlke, ; Dudkiewicz, ; Shields, ). The ideals of promoting person‐centered care and being caring promoted within nursing education may set nurses set up to feel like a failure when they find themselves in healthcare institutions where efficiency and objectivity are of more value (Dahlke et al, ; Dahlke & Stahlke, ).…”
Section: Lack Of Emphasis On the Full Breadth Of Nursing Workmentioning
confidence: 99%